Lithogeochemical characterization of the volcanoes of the La Bocana and San Lorenzo formations in the department of Piura - Rivera, Hugo (2016)
The objective of the present investigation is to expand the geological knowledge and understanding of the geochemical composition of magmatism in the northern Peruvian Andes and to contribute geochemical knowledge in the different geotectonic environments in which igneous rocks are located. The San Lorenzo Formation is made up of mafic rocks and the Bocana of felsic rocks, both of which are sub-alkaline and of the low to medium K-alkaline series, representing a bimodal composition. Likewise, both are metaluminous and have a positive correlation with Na2O and K2O and a negative correlation with the rest of the other oxides. Positive Ce and Th anomalies can be seen in both formations that indicate a relationship to the plate subduction tectonic framework, to the field of Arco de Islas granitoids, to type “I” granitoids and to the field of Volcanic Arc. The depth of the magmatic source was formed within a crust not greater than 20 km and with respect to age (relative age) both formations are contemporary. Both formations are considered as wet magmas but with little melting of water from mafic and metaluminous sources. Based on the oxidation and the water content, they have, and according to their oxygen transience, indicate wet magmas and have a predisposition to be associated with calcophilic elements and with the probability of presenting occurrences of polymetallic deposits.